(untitled) (JournalNX - A Multidisciplinary Peer Reviewed Journal, 2022)
This article explains the main features and characteristics of female and male political discourse. Also, comparative analysis of significant differences between femininity and masculinity in political speech are reflected, particular points to consider about the content and meaning of the political discourse matters are listed in this paper.